Development, measurement and validation of supply chain performance measurement (SCPM) scale in Indian retail sector. Issue 1 (1st February 2016) - Gawankar, Shradha; Kamble, Sachin; Raut, Rakesh
Abstract : Purpose: – The purpose of this paper is to develop a scale with a high degree of reliability, validity and dimensionality which help to determine appropriate supply chain performance measurement (SCPM). Design/methodology/approach: – The data were compiled and collected from 213 operations and supply chain heads from leading retail stores in India. Confirmatory factor analysis was used to test the validity of the proposed measurement scale. Findings: – The major contribution of the present study is the development of SCPM constructs as well as a rigorously validated measurement instrument. The confirmation process is according to the typical standards of scale development. Research limitations/implications: – This paper strives to contribute to the literature on the SCPM in Indian retail industry. This paper tests the validity of the measurement scales which will enable the managers to determine the appropriate SCPM. Practical implications: – In the long run a good set of identified SCPM and their implementation would inevitability enables in deriving meticulous supply chain strategies. Social implications: – SCM managers in evaluating their current supply chain performance. This can help the managers to identify the strengths and weaknesses of their supply chain. Originality/value: – This study proved that the SCPM can be used from different perspectives, all of which are integrated into one exclusive assessment instrument, applied to the SCPM in this case.